(untitled) (Fiep Bulletin - online, 2011)
Contrology focus on body-mind harmony and combines strength with gentle movements, differentiating itself from the traditional exercise techniques. This study evaluated the effect of Pilates and posture exercise programs on the improvement of body flexibility in young men. The Pilates and Posture exercise groups had 14 and 22 participants, respectively, with similar mean age (22.72 ± 1.93 years and 22.09 ± 1.57 years, respectively), mean weight (75.66 ± 7.87 kg and 76.88 ± 8.78 kg, respectively), and mean height (175.59 ± 6.25 m and 176.38 ± 7.18 m, respectively). Student’s t-test for paired samples was used to compare baseline and endpoint results within groups. Student’s t-test for independent samples was used for comparisons between groups. All tests were performed at a significance level of 0.05. There was a significant (p<0.05) improvement in the flexion of the right shoulder and passive flexion of the right hip in the Pilates group (13.50 ± 6.29 and 22.42 ± 3.20, respectively) compared with the Posture group (8.22 ± 2.59 and 18.54 ± 2.72, respectively). The Pilates exercise program was more effective in improving shoulder and hip flexibility than the posture exercise program.